Achieve Sustainable Development in 5G Mobile Technology - , Tarek R. S. Al Aga; , Raba M. Abdalkarim (Archives of Current Research International, 2018)
The next step in the evolution of mobile communication is 5G, and it's a key of the component of the future networked society. With capabilities such as massive system capacity, higher data rates, very low latency and ultra-high reliability, 5G will provide significantly enhanced the mobile-broadband experience but also support a wide range of new wireless applications and use cases. Sustainable development will lead to changes in the way mobile and wireless communication systems are used. As well as the rational exploitation of natural resources and the maintenance of ecological balance, taking into account the interests of future generations Essential services such as e-banking, eLearning, and e-health will continue to proliferate and become more mobile. On-demand information and entertainment (e.g., in the form of augmented reality) will progressively be delivered over mobile and wireless Communication systems. These developments will lead to an avalanche of mobile and wireless traffic volume, predicted to increase a thousand-fold over the next decade. As the deployment and commercial operation of 4g systems are speeding up, technologists worldwide have begun searching for next-generation wireless solutions to meet the anticipated demands in the 2020 era given the explosive growth of mobile internet. this study presents our perspective of the 5G technologies (Fifth generation technologies) With achieving sustainable development By network capacity be significantly increased while network power consumption is decreased. Sustainable development is achieved investigated through five interconnected areas of research: energy efficiency and spectral efficiency co-design, no more cells, rethinking signalling/control, invisible base stations, and full duplex radio. In this paper, we describe the scenarios identified for driving the Fifth generation research direction, integration for new radio concepts, such as massive MIMO ( Multiple Input-Multiple Output), ultradense networks, moving networks, and device-to-device, ultrareliable, and massive machine communications, will allow Fifth generation technologies to support the expected increase in mobile data volume while broadening the range of application domains that mobile communications can support beyond 2020. Furthermore, we give initial directions for the technology components (e.g., link level components, multimode / multi-antenna, multi-RAT(multiple Radio Access Technologies), and multi-layer networks and spectrum handling) that will allow the fulfilment of the requirements of the identified Fifth generation technologies scenarios.